Hydrocarbon Identification through Acoustic Impedance and Elastic Impedance Cross-Correlation using Constrained Sparse Spike Inversion Method - Saraswati, Putu Ayu; Susilo, Adi; Hosni, Farid (Department of Physics - Faculty of Science, 2014)
Among other interpretation methods used in oil and gas industries, seismic inversion has become a method widely practiced to get better understanding on the subsurface condition. By combining seismic and well log data and applying certain workflow, information regarding hydrocarbon distribution presented in the form of impedance section. Using constrained sparse spike inversion, a generated low frequency model was use as input for inversion process to obtain acoustic impedance and elastic impedance variation based on seismic and low frequency data from well log data. To enhance the difference between sand and shale presence, the gamma ray distribution between acoustic impedance (AI) and elastic impedance (EI) generated from the inversion process are cross-correlated. Based on the cross plot, gas sand bodies detected in the area was mapped. Keywords: inversion, acoustic impedance, elastic impedance